Dual Citizenship in Germany and what it Means for World Politics - M. S. Salkina (Vestnik MGIMO-Universiteta)
The article is devoted to the new law on dual citizenship in Germany and analyzes its eventual impact on the international political system. Dual citizenship establishes political and legal connections between an individual and two states at the same time. Its admissibility has been a subject of various discussions since the very appearance of this institution and doubtful loyalty has always been the main argument against it. The adoption of a law permitting dual citizenship in Germany for those whose both parents are foreigners means passing another stage of liberalization. This decision is part of the idea of an open multicultural society officially praised all over Europe and that has silenced (at least for now) arguments on unreliability of those who hold two ID cards. The author focuses on Turkish diaspora that will benefit the most from the initiative, since it is the largest and the most influential foreign community on German territory. Thus, issues related to citizenship are closely connected with modern migration problems. Suggesting that migration flows from Turkey will grow and so will the proportion of German citizens of Turkish descent, the author attempts to predict how the new law can influence world politics. In these circumstances further changes are possible in integration processes, the relations between EU and its key partners and equally in international security architecture. The analysis is preceded by a short historical overview of Turkish diaspora formation in Germany and German vision of a national community that inevitably determines the State citizenship policies.